Magnetic Domain Structure in Ferromagnetic Kagome Metal DyMn6Sn6 - Chen, Zhaohui; Li, Miao; Liu, Caixing; Ma, Zongwei; Han, Yuyan; Gao, Jianhua; Wei, Wensen; Sheng, Zhigao; Du, Haifeng (Frontiers in Physics, 2021)
Two types of magnetic domains, that is, type-I domain belt domain and type-II new stripe domain, are observed in a kagome metal DyMn6Sn6 by microscopic magneto-optic Kerr imaging technique. From 255 to 235 K, the spin reorientation is observed directly in DyMn6Sn6. We analyze the structure of two types of domains through brightness distribution of the images. The type-II domain exists from 235 to 160 K by zero-field cooling (ZFC). At the same time, type-I domain and type-II domain coexist and transform into each other with variation of temperature. Type-II domains can easily transform into type-I domains when the temperature and magnetic field changes, and this process is irreversible. These results demonstrate that the type-I domain is more stable than the type-II domain. The phase diagram of magnetic domains in DyMn6Sn6 is obtained.